Trauma-responsive family engagement in early childhood practices for equity and resilience - Nicholson, Julie; Kurtz, Julie; Rivas, Laura; Henneman, Tasha; Peterson, Eric; Bryant, Shawn; Lin, Betty (Abingdon, Oxfordshire New York Routledge, 2022)
"Designed for all professionals working with parents and families of young children, this practical guide offers comprehensive resources for building trauma-responsive family engagement in your school or program. Throughout this book, you'll find: Evidence-based practices that promote trauma-response family engagement. Exercises and tools for identifying the strengths and learning edges within your program, school, or agency. Vignettes from people and programs striving to create trusting, asset-focused partnerships with families that improve equity and promote culturally responsive practices. Reflective inquiry questions and sample conversations to help you examine your own practices. With concrete examples and easy-to-implement strategies, this critical book helps readers put theory into practice while providing essential support for individuals and groups both new to and experienced with trauma-responsive practices in early childhood."
Includes bibliographical references.
Keywords: Psychic trauma in children -- Treatment; Family social work